2019
DOI: 10.1002/cncr.32460
|View full text |Cite
|
Sign up to set email alerts
|

Time to tackle the blood‐brain barrier in HER2‐mutant lung cancer

Abstract: Growing evidence supports potential differences in the frequencies of brain metastases across distinct oncogenic subsets of non–small cell lung cancer. Insights into these different patterns of brain metastases may help to inform neuroimaging surveillance recommendations and facilitate drug development for more brain‐penetrant targeted therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…These studies highlighted the importance of developing HER2 -targeted agents with higher ability to penetrate the blood-brain barrier. 25 Moreover, lung adenocarcinomas with HER2 mutations exhibit a more aggressive behavior on enhanced computed tomography compared with KRAS - and EGFR -mutant controls, and show a more frequent nodal metastatic spread compared with KRAS -mutant controls. 26 A case report described a lung adenocarcinoma patient with lymphangitic spread and psammoma bodies harboring an HER2 exon 20 insertion mutation.…”
Section: Consensus On Her2 Alterations In Nsclcmentioning
confidence: 99%
“…These studies highlighted the importance of developing HER2 -targeted agents with higher ability to penetrate the blood-brain barrier. 25 Moreover, lung adenocarcinomas with HER2 mutations exhibit a more aggressive behavior on enhanced computed tomography compared with KRAS - and EGFR -mutant controls, and show a more frequent nodal metastatic spread compared with KRAS -mutant controls. 26 A case report described a lung adenocarcinoma patient with lymphangitic spread and psammoma bodies harboring an HER2 exon 20 insertion mutation.…”
Section: Consensus On Her2 Alterations In Nsclcmentioning
confidence: 99%
“…Similar to NSCLC patients with EGFR mutation and ALK gene arrangement, HER2-mutated NSCLC patients do not benefit from immunotherapy. Lin et al 59 suggested that the tumor microenvironment lacking CD8+ T cell infiltration may explain the poor efficacy of ICIs in the treatment of EGFR and HER2-driven NSCLC.…”
Section: Her2 Mutation In Nsclcmentioning
confidence: 99%
“…Several studies have suggested potential differences in the frequencies of brain metastases across the different oncogenic drivers in NSCLC[ 85 ]. NSCLC harboring alterations in EGFR, ALK , or ROS1 have been associated with increased frequencies of brain metastases[ 86 - 89 ].…”
Section: Patterns Of Nodal and Distant Metastasesmentioning
confidence: 99%